2013
DOI: 10.2214/ajr.12.9275
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Residual Disease Using Breast MRI After Excisional Biopsy for Breast Cancer

Abstract: Although the overlapping features of the postsurgical changes and malignant lesions remain as the limitations, dynamic contrast-enhanced breast MRI is a useful tool for residual disease prediction after excisional biopsy for breast cancer. Combined use of morphologic and kinetic evaluation parameters improved the diagnostic performance. We do not recommend that MRI be unreasonably delayed after excisional biopsy considering the risk of prolonging definitive surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 30 publications
0
25
1
1
Order By: Relevance
“…Previous studies have investigated breast MRI findings in patients who have undergone both surgery and radiation. 11,12,17 To the best of our knowledge, our study is the first to report, as a separate group, patients who underwent surgical excisional biopsy but not radiation treatment. We observed that postoperative enhancement developed significantly less often in patients who had undergone surgery alone, compared with patients who had undergone both surgery and radiation.…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations
“…Previous studies have investigated breast MRI findings in patients who have undergone both surgery and radiation. 11,12,17 To the best of our knowledge, our study is the first to report, as a separate group, patients who underwent surgical excisional biopsy but not radiation treatment. We observed that postoperative enhancement developed significantly less often in patients who had undergone surgery alone, compared with patients who had undergone both surgery and radiation.…”
Section: Resultsmentioning
confidence: 85%
“…Radiation treatment also plays an important role in the histopathologic changes of the postconservation breast. Previous studies have investigated breast MRI findings in patients who have undergone both surgery and radiation . To the best of our knowledge, our study is the first to report, as a separate group, patients who underwent surgical excisional biopsy but not radiation treatment.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…It makes valuable contributions in high-risk screening; evaluating the extent of disease, positive surgical margins, and response to neoadjuvant chemotherapy; as well as distinguishing postoperative scar from recurrent disease. [1][2][3][4][5][6] Although the examination is focused on the breast, portions of the neck, thorax, and upper abdomen are also visualized. Just as in computed tomography, the issue of the incidental or unexpected finding must be addressed by the reader.…”
mentioning
confidence: 99%